PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA, DAN STRES KERJA TERHADAP KINERJA KARYAWAN - Widyakto, Adhi; Nurrohmah, Nanda; triyani, dian; Prapti NSS, Rr Lulus (ITB AAS Indonesia Surakarta, 2024)
The source of human labor in an industry is a driving factor based on the number of activities that must be carried out, which explains that without labor an industrial activity cannot run well and according to the goals that have been made. Human resources are also the main key in the process of industrial activities and crucial in achieving the continuity of industrial activities. PT Artha Kayu Indonesia is one industry that struggles with low employee performance. Based on the attendance rate data obtained from HRD, Artha Kayu Indonesia showed a significant decrease in fluctuations. So the author needs to do research on what efforts are made to improve employee performance at Artha Kayu Indonesia so that employees come more often with a predetermined time. The purpose of this study is to determine the effect of Work Discipline, Work Environment and Work Stress on employee performance at Artha Kayu Indonesia. The population in this study is employees of Artha Kayu Indonesia. Based on the sample criteria set, a sample was obtained in this study as many as 100 respondents. The analytical methods used in this study are instrument tests (validity tests and reliability tests), classical assumption tests include (normality tests, heterokedasticity tests, multicollinearity tests), multiple linear regression tests, partial tests (t tests), F test model accuracy, coefficient of determination (R2) tests used to analyze primary data in this study conducted with the help of SPSS version 25. Based on the results of the study shows that there is an influence of work discipline, Work Environment on employee performance, while work stress has no influence on employee performance at Artha Kayu Indonesia. The more positive work discipline, the more employees will comply with the regulations in the Company and will improve employee performance, vice versa if there are many positive Work Environments in the employee work environment, employee performance will increase as a result, also meet predetermined targets. The lower the employee's work stress rate, the higher the employee's performance results.